2018
DOI: 10.3390/v10030130
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Chimeric Lyssaviruses to Assess Vaccine Protection against Highly Divergent Lyssaviruses

Abstract: Lyssaviruses constitute a diverse range of viruses with the ability to cause fatal encephalitis known as rabies. Existing human rabies vaccines and post exposure prophylaxes (PEP) are based on inactivated preparations of, and neutralising antibody preparations directed against, classical rabies viruses, respectively. Whilst these prophylaxes are highly efficient at neutralising and preventing a productive infection with rabies virus, their ability to neutralise other lyssaviruses is thought to be limited. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Growth kinetic assessment of this virus revealed that despite a successful virus rescue, endpoint titres achieved were significantly different with cSN-KBLV reaching a lower final titre compared to the parent cSN virus (Figure 1). However, the titre achieved was still higher than titres achieved in previous studies whereby more divergent glycoproteins were introduced into the same cSN backbone [31]. Decreased viral fitness of cSN-KBLV may be a result of cSN being more adapted to cell culture or a result of the parent virus (KBLV) being less able to replicate in cell culture models than the recombinant virus.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Growth kinetic assessment of this virus revealed that despite a successful virus rescue, endpoint titres achieved were significantly different with cSN-KBLV reaching a lower final titre compared to the parent cSN virus (Figure 1). However, the titre achieved was still higher than titres achieved in previous studies whereby more divergent glycoproteins were introduced into the same cSN backbone [31]. Decreased viral fitness of cSN-KBLV may be a result of cSN being more adapted to cell culture or a result of the parent virus (KBLV) being less able to replicate in cell culture models than the recombinant virus.…”
Section: Discussionmentioning
confidence: 60%
“…Harvested virus was titrated in which the cSN-KBLV grew to a peak titre of 2.5 × 10 4 ffu/mL whilst the parent cSN strain grew to a peak titre of 1.6 × 10 6 ffu/mL. Both values, however, are comparable to similar studies using EBLV-1, EBLV-2 G, IKOV G, and WCBV G within a cSN vector [30,31].…”
Section: Virus Rescue and Titrationmentioning
confidence: 54%
See 2 more Smart Citations
“…There are a variety of ways to broaden a vaccine’s protective breadth, some of which have been attempted for lyssaviruses. A straightforward approach is to create multiple vaccine constructs, each expressing a separate lyssavirus G ( Evans et al., 2018b ), but this strategy would multiply the cost of a vaccine already deemed too expensive for the regions that need it most ( van de Burgwal et al., 2017 ). Furthermore, one lyssavirus G might be immunodominant over others.…”
Section: Discussionmentioning
confidence: 99%